Determinants of corporate philanthropy in Pakistan - Muhammad Abdul Majid Makki; Suleman Aziz Lodhi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2008)
The importance of corporate philanthropy and its related philosophy of corporate social responsibility have captured the attention of researchers and humanitarian groups in WTO era. Corporate donations have been considered as a critical tool to improve corporate image in a highly competitive environment. This paper explores the determinants of corporate donations based on LSE-25 index companies over the five year period 2002-06. Multiple regression techniques have been used for gauging the determinants of corporate philanthropy after collecting data from audited financial reports of companies. The study is a pioneering attempt in measuring the determinants of philanthropy in corporate sector of Pakistan.
Keywords: 330; corporate philanthropy; charitable contributions; LSE-25; corporate donations